Binder-free SiO2 nanotubes/carbon nanofibers mat as superior anode for lithium-ion batteries. (1st February 2022) - Si, Linqi; Yan, Kun; Li, Changle; Huang, Yanfang; Pang, Xinchang; Yang, Xiaomeng; Sui, Dong; Zhang, Yongsheng; Wang, Jianshe; Charles Xu, Chunbao
Highlights: SiO2 nanotubes/carbon nanofibers mat was prepared as a binder-free anode for lithium-ion battery. Hollow and porous SiO2 nanotubes relieve the volume expansion during lithiation/delithiation. Mesoporous bio-based carbon nanofibers buffer volume change and shorten Li + diffusion path. The highly flexible electrode exhibited superior electrochemical performance. Abstract: Silica (SiO2 ) with high specific capacity and low cost is a promising anode for lithium-ion batteries (LIBs), whereas its application is challenged by the substantial volume expansion and poor electrical conductivity. Phenolated and depolymerized lignin furfural (PDLF) resin as renewable carbon precursor, and hollow SiO2 nanotubes are thus designed to address these challenges. Herein, we synthesize the free-standing SiO2 nanotubes@carbon nanofibers (SNTs@CNFs) mat via electrospinning. From the nano-scale morphology, SNTs are embedded into the interior and surface of CNFs along with the fiber framework. The hollow and porous SiO2 nanotubes relieve the volume expansion during the lithium-ion insertion/extraction. Meanwhile, the interconnected bio-based CNFs improve the electrical conductivity and shorten the lithium-ion diffusion path. The SNTs@CNFs mat exhibits excellent mechanical flexibility and is used as a free-standing anode without any binders, carbon black, and current collectors, it delivers an ultra-high reversible capacity of 1067 mAh g −1 at the current density of 100 mA g −1 after 300 cycles. Even at a high current density of 1000 mA g −1, it remains a reversible capacity of 562 mAh g −1 after 700 cycles. This work marks an important exploration for next-generation high-energy density LIBs and other flexible energy storage devices. Graphical Abstract: Graphical Abstract Image, graphical abstract .